1990
DOI: 10.1038/bjc.1990.404
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of isolated liver perfusion versus hepatic artery infusion with mitomycin C in rats

Abstract: Summary Systemic toxicity is usually the dose-limiting factor in cancer chemotherapy. Regional chemotherapy is therefore an attractive strategy in the treatment of liver metastasis. Two ways of regional chemotherapy, hepatic artery infusion (HAI) and isolated liver perfusion (ILP), were compared investigating the difference in toxicity with tissue and biofluid concentrations of mitomycin C (MMC). In wistar derived WAG rats the maximally tolerated dose of mitomycin C via HAI was 1.2 mg kg-'. Body weight measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…The differences in the results of this study with melphalan and a previously published study with MMC (Marinelli et al, 1990a) will be discussed.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…The differences in the results of this study with melphalan and a previously published study with MMC (Marinelli et al, 1990a) will be discussed.…”
mentioning
confidence: 81%
“…Only with MMC complete remissions and a significantly prolonged survival has been reported (Marinelli et al, 1991). In rats, hepatotoxic side effects of MMC was dose limiting (Marinelli et al, 1990a). In six out of seven evaluable patients treated with 30 mg m-2 of MMC in ILP an objective response was seen (> 50% tumour volume reduction on CT).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Isolated liver perfusion and hepatic artery infusion are described elsewhere (Marinelli et al, 1990). Briefly: in the isolated liver perfusion two inflow limbs of the isolated circuit were established by cannulation of the pyloric branch of the portal vein and the gastroduodenal branch of the common hepatic artery.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…In this study, we evaluated the effect of mitomycin C, which has a steep dose-response relationship (Mitra & Maillova, 1986;Wallner & Li, 1987;de Bruijn et al, 1988) and has been reported to be a promising drug for colorectal cancer (Doll et al, 1985;Schneider et al, 1989). In a previous study (Marinelli et al, 1990), it was determined that in isolated liver perfusion a four times higher dose of mitomycin C could be administered than via hepatic artery infusion, resulting in a five times higher concentration in tumour tissue. In the present study, we investigated whether this higher tissue concentration is also more effective in the actual elimination of tumour cells.…”
mentioning
confidence: 99%